Lactation performance of dairy cows on feeding rumen-protected choline - LUNAGARIYA, PRAVIN M; SHAH, SHAILESH V; PATEL, YOGESH G`; PATEL, JIGAR H (The Indian Journal of Animal Sciences, 2023)
The experiment was designed to assess the effect of supplemental feeding of 40 g/day rumen-protected choline (33.5% w/w) in the total mixed ration of lactating cows on nutrient intake, lactation, reproduction, feed efficiency, and feed cost during 294 days of the lactation. The study was conducted at Livestock Research Station, Anand during 2018 to 2021. A total of sixteen cows were randomly distributed into two groups of eight each based on descending order of previous standard lactation yield and lactation numbers. An intake and milk yield were calculated for 1-21 biweekly periods. The milk composition was assessed four times during lactation. The body condition score (BCS) on a 1-5 point scale with an increment of 0.25 points was measured at -21, -14, -7, 0, 7, 14, 21, 35, 49, 63, 91, and 119 days of calving. The supplemental feeding of rumen-protected choline (RPC) in T2 group resulted in lower nutrient intake, lesser insemination to conceive, and service period with higher 4% fat corrected milk (FCM) yield in dairy cows. The body condition score and milk yield persistency were higher along with improved feed efficiency and feed economics in the T2 group as compared to the T1 group. The daily feeding of 40 g RPC during -21 to 120 days of calving resulted in significantly lower nutrient intake with improved 4% FCM yield, reproductive performance, feed efficiency, and feed economics in dairy cows.